Best Answer

If you mean: 6x-y = 33 and 6x+3y = 45

So by eliminating 6x in both equations by subtracting: 4y = 12 => y =3

Therefore by substitution: x = 6 and y = 3

Remember: --y+3y = 4y

Q: Using elimination how would you solve 6x-y 33 6x plus 3y 45?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

By elimination: x = 3 and y = 0

You cannot solve one linear equation in two variables. You need two equations that are independent.

(2,-2)

The given expression can't be solved as equations because there are no equality signs.

Yes and it works out that x = 3 and y = 4

Related questions

By elimination: x = 3 and y = 0

You cannot solve one linear equation in two variables. You need two equations that are independent.

(2,-2)

The given expression can't be solved as equations because there are no equality signs.

Yes and it works out that x = 3 and y = 4

16

With great difficulty because without any equality sign the given terms can't be considered to be an equation.

No. Solving equations in two unknowns requires two independent equations. Since you have only one equation there is no solution.

The elimination method only works with simultaneous equations, hence another equation is needed here for it to be solvable.

y=16 x= -4

The answer is that it cannot be done. To solve a set of equations in k variables (in this case, 2) you need at least two independent equations.

You could multiply the first equation by 3 and the second by -5 and eliminate the x... OR you could multiply the first equation by 7 and the second by 10 and eliminate the y. Either way works.